MENGELOLA KONFLIK DALAM RUMAH TANGGA; CATATAN KECIL SEBUAH PERNIKAHAN DALAM ISLAM - Sati, Ali (IAIN Padangsidimpuan, 2020)
This paper discusses techniques and ways of dealing with problems in the household, which at the core of the problem in this paper is how to manage conflict in the household according to Islamic teachings. To answer this problem, the author uses qualitative methods through the Qur'an and the hadiths of the Prophet Muhammad which tell about solutions to overcome conflicts in the household.In this paper, the author finds that Rasulullah SAW provides many descriptions in managing conflicts in the household, even the concepts put forward by the Prophet Muhammad have been popularized by intellectuals of the New Age, of course, with different language editors.This study is very interesting to discuss, especially in the era of the Covid 19 pandemic because at this time the economy in Indonesia was affected by the pandemic, yet other aspects were exacerbated by Cocid 19 so that it also resulted in conflicts within households which inevitably had to be addressed wisely .